2018
DOI: 10.1016/j.cognition.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Numerical cognition is resilient to dramatic changes in early sensory experience

Abstract: Humans and non-human animals can approximate large visual quantities without counting. The approximate number representations underlying this ability are noisy, with the amount of noise proportional to the quantity being represented. Numerate humans also have access to a separate system for representing exact quantities using number symbols and words; it is this second, exact system that supports most of formal mathematics. Although numerical approximation abilities and symbolic number abilities are distinct i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 91 publications
(137 reference statements)
2
13
0
2
Order By: Relevance
“…However, for many math tasks, including those that activate "visual" cortex in blindness, there are no blindness-related advantages (e.g. Crollen et al, 2019, Kanjlia et al, 2016, Kanjlia et al, 2018). In the current study, the blind group performed no different from the sighted on a timed subtraction task and less well than the sighted on a timed division task.…”
Section: Blindness Confers An Advantage On a Sentence Comprehension Tmentioning
confidence: 99%
“…However, for many math tasks, including those that activate "visual" cortex in blindness, there are no blindness-related advantages (e.g. Crollen et al, 2019, Kanjlia et al, 2016, Kanjlia et al, 2018). In the current study, the blind group performed no different from the sighted on a timed subtraction task and less well than the sighted on a timed division task.…”
Section: Blindness Confers An Advantage On a Sentence Comprehension Tmentioning
confidence: 99%
“…Congenitally blind individuals show similar or slightly better performance than sighted individuals when estimating numbers of tones, footsteps or finger taps, and performance is ratio-dependent in both groups . Prior studies also find that, like people who are sighted, individuals who are congenitally blind recruit the IPS during symbolic number reasoning and show similar behavioral correlations between numerical approximation and symbolic math performance across individuals (Amalric et al, 2017;Crollen et al, 2019;Kanjlia, Feigenson, et al, 2018;Kanjlia et al, 2016). Together, these findings suggest that numerical representations are established in the IPS independent of gross differences in sensory experience.…”
Section: Ips Representations Of Number and Visual Experiencementioning
confidence: 60%
“…However, evidence suggests that children presented with difficult approximate numerical discriminations perform better when presented with redundant visual and auditory input, compared to only visual input, suggesting that auditory tones are not simply treated as indicating the presence of visual objects ( Posid and Cordes, 2019 ). Furthermore, people blind from birth succeed at purely auditory ANS tasks ( Kanjlia et al, 2018 ), showing that ANS representations can be generated in the total absence of any visual experience. Still, despite the above findings, it is impossible to entirely rule out an account by which visualization plays some role in the processing of auditory input – something that is currently the topic of much ongoing debate ( De Volder et al, 2001 ; Amedi et al, 2005 ; Vetter et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The third aim was to ask whether the link between ANS precision and school math abilities reflects individual differences in an abstract, modality-neutral sense of approximate number, or if instead the correlation is explained entirely by a link between math and visuospatial abilities (i.e., subsymbolic-symbolic transfer). Kanjlia et al (2018) found that ANS precision for auditory sequences correlated with math performance in blind and sighted adults. But, it remains unknown whether there is a visually independent link between the ANS and math ability early in development.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation